Testing experience and environmental enrichment potentiated open-field habituation and grooming behaviour in rats - Rojas Carvajal, Mijail (2018)
In laboratory rats, one of the most used paradigms to assess habituation to novelty is the open-field test. Environmental enrichment has proved to be a reliable way to enhance open-field test habituation. Experiment 1, therefore, was designed to test whether grooming behaviour in the open-field test increases concomitantly with the habituation of exploratory behaviours (locomotion and rearing behaviour, an alert upright posture). To this aim, after a baseline measure, rats were raised in environmentally enriched and standard housing conditions and then tested 30 and 60 days later. As some grooming subtypes are differentially displayed in the open-field test, we hypothesized that only the grooming subtype that included longer and more complex sequences (e.g. body licking) would increase with habituation. We found that environmental enrichment enhanced short-term (within days) and longterm (between days) open-field test habituation, and increased grooming, particularly body licking. To provide evidence that grooming in the open-field test is part of the habituation process and not a byproduct of environmental enrichment, habituation was promoted by exposing a different group of rats that had been reared in standard housing to four consecutive open-field tests in experiment 2. We supposed that the diminution of exploratory open-field test behaviours would be accompanied by an increase in body licking. We found that as locomotion and rearing behaviour decreased, body licking increased gradually both within and between days, suggesting that the appearance of more complex and longer grooming sequences are part of a de-arousal inhibition system subserving novelty habituation. A detailed analysis of grooming, therefore, may provide information about the emotional state of the rat that cannot otherwise be obtained from assessing exploratory activity.